A Model of Portfolio Delegation and Strategic Trading - Kyle, Albert S.; Ou-Yang, Hui; Wei, Bin (Review of Financial Studies, 2011)
This article endogenizes information acquisition and portfolio delegation in a one-period strategic trading model. We find that, when the informed portfolio manager is relatively risk tolerant (averse), price informativeness increases (decreases) with the amount of noise trading. When noise trading is endogenized, the linear equilibrium in the traditional literature breaks down under a wide range of parameter values. In contrast, a linear equilibrium always exists in our model. In a conventional portfolio delegation model under a competitive partial equilibrium, the manager's effort of acquiring information is independent of a linear incentive contract. In our strategic trading model, however, a higher-powered linear contract induces the manager to exert more effort for information acquisition. The Author 2011. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.